2011
DOI: 10.3892/ol.2011.395
|View full text |Cite
|
Sign up to set email alerts
|

Emetine regulates the alternative splicing of caspase 9 in tumor cells

Abstract: Abstract. Exons 3 to 6 in the caspase 9 gene undergo alternative splicing in which the larger caspase 9 splice variant promotes apoptosis, in contrast to the dominant negative anti-apoptotic splice variant, the smaller caspase 9b. In this study, the regulation of the alternative splicing of caspase 9 pre-mRNA was examined in response to Emetine. Treatment of C33A cells, breast cancer MCF-7 cells and MCF-7/Adr cells with Emetine dihydrochloride upregulated the level of smaller caspase 9b mRNA and concomitantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…By contrast, pretreatment with the PP1 inhibitor OA could partially restore the effects of BS008 on the phosphorylation levels of SRSF3 as well as the AS of HIPK3 and SMAC transcripts. These results are similar to those of other reports that revealed that 4β‐hydroxywithanolide E (Lee et al ., ), ceramide (Chalfant et al ., ; Massiello et al ., ), emetine (Boon‐Unge et al ., ; Pan et al ., ), and epigallocatechin‐3‐gallate/ibuprofen can modulate (Kim, ) the AS of apoptotic gene transcripts through a PP1‐mediated splicing mechanism. These publications imply that PP1 plays a crucial role in regulating the AS of apoptotic gene transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, pretreatment with the PP1 inhibitor OA could partially restore the effects of BS008 on the phosphorylation levels of SRSF3 as well as the AS of HIPK3 and SMAC transcripts. These results are similar to those of other reports that revealed that 4β‐hydroxywithanolide E (Lee et al ., ), ceramide (Chalfant et al ., ; Massiello et al ., ), emetine (Boon‐Unge et al ., ; Pan et al ., ), and epigallocatechin‐3‐gallate/ibuprofen can modulate (Kim, ) the AS of apoptotic gene transcripts through a PP1‐mediated splicing mechanism. These publications imply that PP1 plays a crucial role in regulating the AS of apoptotic gene transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Gemticabine was found to downregulate the expression of caspase‐9b in A549 cells . Emetine was found to regulate caspase‐9 splicing showing differential splicing pattern in different cell types …”
Section: Anticancer Drugs and Alternative Splicingmentioning
confidence: 91%
“…Calyculin A, an inhibitor of both PP1 and PP2A, was found to block the emitine effects on caspase‐9 splicing in C33A and PC3 cells, while okadaic acid which is a selective inhibitor of PP2A showed no effect. Hence, it was concluded that emitine exerts its affect through PP1‐dependent mechanism . However, emitine showed opposite effect on caspase‐9 splicing in C33A and PC3 cells .…”
Section: Mechanisms Of Alternative Splicing Modulation By Anticancer mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas caspase 8 is normally proapoptotic, an intron retention forms Cas8L with antiapoptotic properties (Himeji et al, 2002). Skipping of exons 3, 4, 5, and 6 in caspase 9 results in a shorter protein that also has antiapoptotic properties—this event being regulated by SRSF1 and SRSF2 (Shultz et al, 2010; Pan et al, 2011). Yet another type of AS—5′ alternative splice sites—is responsible for a proapoptotic isoform of the well-known survival factor Bcl-xL, termed Bcl-xS (Cloutier et al, 2008).…”
Section: Pathways Regulated By Alternative Splicingmentioning
confidence: 99%